The health literacy status of youth with disabilities in a residential treatment setting - Huscroft-D’Angelo, Jacqueline N.; Trout, Alexandra L.; Epstein, Michael H; Thompson, Ronald W. (Social Welfare: Interdisciplinary Approach, 2014)
Research has indicated that youth eligible for special education services in residential centers are at an increased risk across many areas including overall health, medication use, academic, behavioral, and familial functioning. Yet it remains unknown how well they are able to read, understand, and use health-related information. The purpose of this study was to investigate the health literacy status of youth receiving special education (N= 61) services at a large residential care facility in the Midwest. Results indicate youth with disabilities are at increased risk of low health literacy in areas of reading recognition and comprehension. Specifically, well over 50% of the sample scored in the possible to likely limited health literacy level. Study limitations, future research, and implications are provided.